Guest

(3+x)/(2x-3) = -1/2 (3+x)/(2x-3) = -1/2 (3+x)/(2x-3) = -1/2 (3+x)/(2x-3) = -1/2 (3+x)/(2x-3) = -1/2 (3+x)/(2x-3) = -1/2(3+x)/(2x-3) = -1/2

(3+x)/(2x-3) = -1/2
(3+x)/(2x-3) = -1/2
(3+x)/(2x-3) = -1/2
(3+x)/(2x-3) = -1/2
(3+x)/(2x-3) = -1/2
(3+x)/(2x-3) = -1/2(3+x)/(2x-3) = -1/2
 

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5963 Points
2 years ago
Dear Student

(3+x)/(2x-3) = -1/2
2 (3 + x) = -1 (2x – 3)

6 + 2x = -2x + 3

4x = 3 -6

x = -3/4

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free